2017
DOI: 10.1002/jcph.867
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism-Based Pharmacokinetic/Pharmacodynamic Model for Bococizumab, a Humanized Monoclonal Antibody Against Proprotein Convertase Subtilisin/Kexin Type 9, and Its Application in Early Clinical Development

Abstract: Bococizumab (RN316/PF-04950615), a humanized monoclonal antibody, binds to secreted proprotein convertase subtilisin/kexin type 9 (PCSK9) and prevents its downregulation of low-density lipoprotein receptor, leading to improved clearance and reduction of low-density lipoprotein cholesterol (LDL-C) in plasma. A mechanism-based drug-target binding model was developed, accounting for bococizumab, PCSK9, and LDL-C concentrations and the effects of concomitant administration of statins. This model was utilized to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Indeed, mean baseline concentrations of PCSK9 were higher in Study 2 (61 ng/mL) compared with Study 1 (40 ng/mL). A recent PK/PD analysis using bococizumab phase I and IIA trial data to construct a mechanism‐based drug–target binding model indicated that coadministration of bococizumab with a statin predicted an increase in LDL‐C clearance in the presence of background statin therapy . Combined with the enhanced bococizumab clearance reported here, these observations are consistent with the proposed effect of statins in stimulating both LDLR and PCSK9 production and the target‐mediated disposition of bococizumab …”
Section: Discussionsupporting
confidence: 87%
“…Indeed, mean baseline concentrations of PCSK9 were higher in Study 2 (61 ng/mL) compared with Study 1 (40 ng/mL). A recent PK/PD analysis using bococizumab phase I and IIA trial data to construct a mechanism‐based drug–target binding model indicated that coadministration of bococizumab with a statin predicted an increase in LDL‐C clearance in the presence of background statin therapy . Combined with the enhanced bococizumab clearance reported here, these observations are consistent with the proposed effect of statins in stimulating both LDLR and PCSK9 production and the target‐mediated disposition of bococizumab …”
Section: Discussionsupporting
confidence: 87%
“…More specifically, single‐dose bococizumab produced maximum LDL‐C reductions of up to 70%, and 100% of subjects receiving bococizumab s.c. 3 mg/kg achieved a ≥ 50% reduction from baseline at day 8. These reductions are in line with data and modeled predictions from other clinical studies of bococizumab, using a similar assay technique …”
Section: Discussionsupporting
confidence: 86%
“…A mechanism-based drug–target binding model using bococizumab Phase I and IIA trial data was developed to account for bococizumab, PCSK9, and LDL-C concentrations, and the effects of co-administration of statins. The model indicated that statins could predict an increase in LDL-C clearance of bococizumab by co-administration, which was consistent with the proposed effect of statins in stimulating both LDLR and PCSK9 production and the target-mediated disposition of bococizumab [83,90]. In July 2016, a Phase I trial for hypercholesterolemia in combination with recombinant human hyaluronidase (rHuPH20) was terminated due to business priorities regarding study execution [91,92].…”
Section: Discontinued Drugsmentioning
confidence: 60%
“…PCSK9 is a serine protease, which bonding to LDL receptor (LDL-R) results in the aggregation of LDL cholesterol (LDL-C), an important factor causing atherosclerotic heart disease. Working as a humanized monoclonal antibody (mAb), bococizumab extracellularly influences circulating PCSK9 either by secluding it or blocking the bonding [83,84].…”
Section: Discontinued Drugsmentioning
confidence: 99%